A simplified preparation method of silicon-substituted calcium phosphates according to green chemistry principles - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2007)
A simplified preparation method of silicon-substituted calcium phosphates with a very high yield (close to 100%) has been elaborated, according to the principles of Green Chemistry. The technique consists of mixing of crystals of calcium nitrate and ammonium dihydrogen phosphate in the desired proportions, following by addition of the necessary amount of a silicon-containing compound. The homogenous mixture is sintered between 900 and 1200 degrees C. Either a silicon-containing hydroxyapatite (Si-HA) or a silicon-stabilized tricalcium phosphate (Si-alpha TCP) can be synthesized, depending on the Ca/P, Ca/(P+Si) and SUP molar ratios.
Keywords: hydroxyapatite; tricalcium phosphate; silica; silicon substitution; bioceramics